NEGOTIATING LINGUISTIC IDENTITY AND BELONGING IN EUROPE (= Nationalisms across the Globe 14). Eds. Virve-Anneli Vihman and Kristiina Praakli: Frankfurt am Main et al.: Peter Lang. 2013. 354 pages. - E. Borowski, Krzysztof; Fisher, Alexandra (Slavia Centralis, 2020)
V prispevku je predstavljena 14. številka knjižne serije Nationalisms across the Globe – Negotiating Linguistic Identity: Language and Belonging in Europe.